2016
DOI: 10.7554/elife.15039
|View full text |Cite
|
Sign up to set email alerts
|

Hawkmoths evaluate scenting flowers with the tip of their proboscis

Abstract: Pollination by insects is essential to many ecosystems. Previously, we have shown that floral scent is important to mediate pollen transfer between plants (Kessler et al., 2015). Yet, the mechanisms by which pollinators evaluate volatiles of single flowers remained unclear. Here, Nicotiana attenuata plants, in which floral volatiles have been genetically silenced and its hawkmoth pollinator, Manduca sexta, were used in semi-natural tent and wind-tunnel assays to explore the function of floral scent. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 37 publications
2
80
2
Order By: Relevance
“…Consistent with an olfactory function and unlike identified Grs, the Or transcripts were predominantly detected in chemosensory tissues such as antennae and maxillary palps, and some of them were also expressed in other tissues. Expression of Ors outside the classical chemosensory tissues has also been reported in other insect species (Bray and Amrein, 2003;Haverkamp et al, 2016;Klinner et al, 2016;Pitts et al, 2014;Raad et al, 2016). Given the generally low expression levels of Ors and that many of the firebrat Ors identified from the genome form clades with silverfish Ors identified from our RNAseq experiments in our phylogenetic analysis, it is likely that many of the firebrat genes described from the genome by Brand and co-workers (2018) are indeed also expressed in the firebrat antennae and that they were missed in previous RNAseq experiments because of insufficient sequencing depth.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with an olfactory function and unlike identified Grs, the Or transcripts were predominantly detected in chemosensory tissues such as antennae and maxillary palps, and some of them were also expressed in other tissues. Expression of Ors outside the classical chemosensory tissues has also been reported in other insect species (Bray and Amrein, 2003;Haverkamp et al, 2016;Klinner et al, 2016;Pitts et al, 2014;Raad et al, 2016). Given the generally low expression levels of Ors and that many of the firebrat Ors identified from the genome form clades with silverfish Ors identified from our RNAseq experiments in our phylogenetic analysis, it is likely that many of the firebrat genes described from the genome by Brand and co-workers (2018) are indeed also expressed in the firebrat antennae and that they were missed in previous RNAseq experiments because of insufficient sequencing depth.…”
Section: Discussionmentioning
confidence: 62%
“…Before the start of the experiment, the proboscis of a moth was dusted with pollen collected the previous day, using a fine brush. On average, this method loaded 548.75 (n = 41, SE = 88.85) pollen grains to a single proboscis, which has previously been shown to lead to seed numbers comparable to those found under natural conditions (Kessler et al 2015, Haverkamp et al 2016b). The moth was then allowed to forage freely on the single antherectomized flower in the wind tunnel for 4 min or until the first successful foraging trial.…”
Section: Pollen Uptake and Deliverymentioning
confidence: 57%
“…M. sexta foraging is an example of a behavior that is mediated by the integration of multiple sensory inputs, combining vision and olfaction to effectively determine the salient stimulus (93, 94). Observations in wind tunnels (with 2-3m distance to the stimulus on release) or free-air fields (10-24m) with natural or semi-natural stimuli, found that presenting the visual stimulus alone would result in M. sexta approaching the source, but did not result in feeding (9, 95). In certain cases, only when an odor accompanied the visual stimulus an approach was followed by foraging attempts (96).…”
Section: Discussionmentioning
confidence: 99%
“…Both visual and olfactory cues of the upright trumpet flower guides foraging decisions, indicated by hovering and an unfurling proboscis (7, 8). The hovering hawkmoth with extended proboscis is capable of close range olfactory (9) and mechanosensory (10) guidance to reach the nectar canals. Field observations find that females intersperse feeding bouts with oviposition (11) and M. sexta females demonstrate innate attraction not only to flowering but also to non-flowering D. wrightii plants (12).…”
Section: Introductionmentioning
confidence: 99%